Dabrafenib and trametinib either in combination or as monotherapy in pediatric patients harboring BRAF alterations in gliomas or other rare tumors: Findings from a managed access program - Mark Russo; AnaRita Ferreira; Michael Roughton; Sviatlana Rizk; Naveen Chhabra; Manar Aoun (EJC Paediatric Oncology)
Background: To enable global access to therapies in countries where suitable formulations and/or indications are not yet approved, managed access programs (MAPs) are established. Herein, we report patient data from a MAP for pediatric patients with BRAF-altered gliomas or other rare tumors, seeking clinical benefit from dabrafenib and/or trametinib. Methods: We analyzed data from global MAP, where pediatric patients with BRAF alterations in gliomas or other rare tumors received dabrafenib and/or trametinib. Key eligibility criteria were age < 18 years, absence of approved alternative therapies, presence of BRAF alterations, and exhausted standard therapies. Requests analyzed in this study were collected from April 2015 to December 2023 (cutoff date). The main objectives were to describe patients’ characteristics and treatment duration. Results: Overall, 863 patients with solid malignancies were included, of which 30.4 %, 23.4 %, and 46.2 % received combination therapy, dabrafenib monotherapy and trametinib monotherapy, respectively. Median age was 6.4 years, and 51 % were male. Most patients had low-grade (80.9 %) or high-grade (5.6 %) gliomas, followed by Langerhans' cell histiocytosis (13.6 %). The median treatment duration (mDoT) was > 12 months (ranged between 12.4 and 45.9 months) irrespective of the treatment groups, disease types, and formulations. At the data cutoff, treatment was ongoing for approximately 47 % of patients. Conclusions: MAP data are a valuable real-world resource for understanding patient characteristics in rare tumors such as pediatric gliomas. A significant number of treatment requests indicate substantial unmet need, and observed mDoT across subgroups suggests potential treatment benefit in these patients. No new safety findings were identified for dabrafenib/trametinib.